The Influence of Leadership Functions, Motivation and Competence on Work Ethic and Its Implications on the Performance of the Sector Police Head in the West Java Regional Police Region - R. Jusdijachlan (DINASTI RESEARCH, 2022)
The purpose of this study was to determine and analyze the influence of the role of leadership, motivation, and competence on work ethic and its implications for the performance of the Sector Police Head in the West Java Regional Police. The research sample used a sampling technique in a cluster proportional random sampling. The data collection method used a questionnaire or questionnaire method. The research method uses descriptive and verification methods with Path Analysis techniques. The results of this descriptive study indicate that the functions of leadership, motivation, competence, work ethics and the performance of the police chief are perceived to be quite good to good. While the results of the verification research prove that the functions of leadership, motivation.